Pendekatan Diversi dalam Sistem Peradilan Pidana Anak (SPPA) - Sausan Afifah Denadin; Andi Najemi; Nys. Arfa (PAMPAS: Journal of Criminal Law, 2021)
This article aims to determine the diversion approach in the juvenile criminal justice system (SPPA) in Batanghari District and obstacles experienced in applying the diversion approach. The formulation of the problem is how the diversion approach in the juvenile justice system (SPPA) in Batanghari District? and what are the obstacles in the application of the diversion approach in the juvenile criminal justice system (SPPA) in Batanghari District? This research uses empirical juridical method. The results of this study are that the diversion approach in Batanghari District has worked quite well at every level of the juvenile criminal justice system (SPPA), but the success rate of implementing diversion at each level is different. This diversion approach has been based on law number 11 of 2012 concerning the juvenile criminal justice system (SPPA) as well as several derivative rules as rules for implementing diversion efforts at each level. The obstacles faced in providing this diversion approach are lack of public understanding of diversion, no agreement between the two parties, the cost of compensation requested by the victim is too large, the constraints on calling the parties, the occurrence of disputes during the diversion process, the perception of the community that each a person who is guilty must be convicted so that it cannot be forgiven only by implementing the diversion agreement, the victim’s family or victim is not present during the diversion process. ABSTRAK Artikel ini bertujuan untuk mengetahui pendekatan diversi dalam sistem peradilan pidana anak (SPPA) di Kabupaten Batanghari dan kendala yang dialami dalam penerapan pendekatan diversi. Rumusan masalahnya adalah Bagaimana pendekatan diversi dalam sistem peradilan pidana anak (SPPA) di Kabupaten Batanghari? dan apa saja kendala dalam penerapan pendekatan diversi dalam sistem peradilan pidana anak (SPPA) di Kabupaten Batanghari? Penelitian ini menggunakan metode yuridis empiris. Hasil penelitian adalah pendekatan diversi di Kabupaten Batanghari sudah berjalan cukup baik di setiap tingkatan sistem peradilan pidana anak (SPPA) hanya saja dalam tingkat keberhasilan dilaksanakannya diversi di setiap tingkatan berbeda-beda. Pendekatan diversi ini sudah berlandaskan dengan Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak (SPPA) serta beberapa aturan turunan sebagai aturan pelaksanaan dari upaya diversi pada setiap tingkatan. Kendala yang dihadapi dalam memberikan pendekatan diversi ini adalah pemahaman masyarakat terhadap diversi masih kurang, tidak adanya kesepakatan antara kedua belah pihak, biaya ganti kerugian yang diminta korban terlalu besar, kendala pemanggilan para pihak, terjadinya perselisihan selama proses diversi, adanya tanggapan dari masyarakat bahwa setiap orang yang bersalah mesti dipidana sehingga tidak dapat dimaafkan hanya dengan pelaksanaan kesepakatan diversi saja, keluarga korban atau korban tidak hadir selama proses diversi.